การศึกษาแรงจูงใจในการเรียนที่มีต่อผลการเรียนของนิสิตแพทย์ มหาวิทยาลัยนเรศวร - เรียนแพง สุดารัตน์; ศิลากุล พิมพ์ประไพ; โรจน์ทนานันท์ สุประวีณ์; กลมกล่อม อัจฉรา; ภูดอนตอง กฤษฎา; ชลดาวารี เอกชัย (Health Science Clinical Research, 2021)
Background : Motivation is an important factor for medical student to educational achievement. Amotivation affects medical students especially worse effective education. The effective education can measure in various pattern which obvious pattern is academic performance. Objective : To assess the influence of motivation on academic performance between medical students. Methods : A cross-sectional study was carried out among a sample groups of 325 medical students from Naresuan University by use an electronic questionnaire. Academic performance was measured by their grade point average (GPA) last semester. Motivation was measured by using Strength of Motivation for Medical school (SMMS-R). Data was analyzed by frequency, percentage, median, interquartile range, Kruskal-Wallis test and gaussian regression. Results : From 325 eligible medical students were found associating between motivation and GPA as over all of motivation’s correlation coefficients was 0.01 (p=0.028) Willingness of sacrifice’s correlation coefficients was 0.01 (p=0.008) Readiness to start’s correlation coefficients was 0.03 (p=0.007) Persistance’s correlation coefficients was 0.02 (p=0.059) Conclusion : The higher level of overall of motivation affect to the better academic performance. The higher level of Willingness of sacrifice, Readiness to start and Persistance affect to the better academic performance.